Co-evolução dos componentes do marco institucional e das trajetórias de acumulação de capacidades tecnológicas no setor de agro-energia (etanol) no Brasil (1970-2009) - Matias, Carlos Alexandre (2011)
This dissertation focuses on examining the evolution of the components of the institutional framework in association with the trajectories of technological capabilities accumulation in production and innovation in industries based on natural resources in emerging economies. This relationship is examined in the Brazilian ethanol industry, in the period between 1970 and 2009. The institutional framework is examined on the basis of macro-institutions (regimes consisting of complex public policies), meso-institutions (the political and bureaucratic structures) and knowledge-based institutions (research institutes and universities). The trajectories of technological capabilities accumulation are assessed based on innovation levels. The dissertation is based on a case study at the sector level. Moreover, the study is based on evidence obtained from various sources, in the industry level, government documents and also draws on secondary evidence at the enterprise level. The main results of this dissertation are: (1) The ethanol industry has reached levels of innovative technological capabilities in two functions. On a scale of 1 to 5, the sector has acquired during the 1st period (1970-1989), industrial technological capabilities (product and process) at Level 3 and, during the 2nd period (1990-2009), the ethanol industry accumulated industrial technological capabilities at Level 5. Regarding the accumulation of technological capabilities in the agricultural area (raw materials), during the 1st period the sector acquired technological capabilities at Level 4 and only in the following period reached Level 5. (2) The institutions have played an important role on the trajectories of technological capabilities accumulation in the Brazilian ethanol industry. Among them, are the R&D activities developed at research based institutions, which have accumulated production and innovation technological capabilities, shared with companies. (3) However, the study points to some vulnerability in the Brazilian ethanol industry regarding its ability to sustain their innovation performance. Among them stands out: (1) large proportion of innovative activities at R&D level is carried out based on external arrangements, with little effort from enterprises activities; (2) despite the massive government effort to develop the sector, this is directed (locked-in) to the trajectory of technological capabilities accumulation of 1st generation ethanol; (3) components of the institutional framework encouraged research activities at universities and research institutes, at bench level, which resulted in experimental designs and inventions; (4) the favorable market conditions, the widespread availability of sugar cane and ethanol/sugar production flexibility contributed to accommodate the ethanol sector and there seems to be a comfort zone in the sector. Thus, the evidence warns about the need for investments in innovative R&D activities within companies (focus on innovations, wealth, and diversifying into other sectors). Therefore, the results of this dissertation may point out suggestions for government officials. The new public policies should: (1) redirect the accumulation strategies of innovative technological capabilities, strongly linked and focused on the support of the trajectories of technological capabilities accumulation to produce ethanol from 1st generation; (2) foster the accumulation of production and innovation technological capabilities in the emerging trajectory to produce ethanol from 2nd generation, currently at an experimental level and widely developed within the knowledge-based institutions, and to diversify products to new sectors and new business lines. The results of this dissertation also suggest to the company managers of the Brazilian ethanol industry: (1) reshape the business strategies in order to expand the innovative activities of enterprises within the ethanol industry, which could result in the creation of innovations in industrial scale; (2) companies of the ethanol industry should take a proactive behavior in order to coordinate the R&D efforts towards the problems and future challenges to be faced by the Brazilian ethanol sector.